Systematic identification and referral of smokers attending HIV ambulatory care highlights the failure of current service provision in an at-risk population. Issue 1 (3rd October 2019) - Brown, James; Kyriacou, Christianna; Pickett, Elisha; Edwards, Kelly; Joshi, Hemal; Stewart, Nafeesah; Melville, Andrew; Johnson, Margaret; Flint, Jan; Bartley, Angela; Rodger, Alison; Lipman, Marc
Abstract : Introduction: People living with HIV (PLWH) are more likely to smoke than the general population and are at greater risk of smoking-related illness. Healthcare services need to address this burden of preventable disease. Methods: We evaluated the impact of a brief intervention that asked service users about smoking when they attended for ambulatory HIV care in London, UK, and offered referral to smoking cessation. Results: Overall, 1548 HIV-positive individuals were asked about their smoking status over a 12-month period. Of this group, 385 (25%) reported that they were current smokers, 372 (97%) were offered referral to smoking cessation services and 154 (40%) accepted this. We established an outcome of referral for 114 (74%) individuals. A total of 36 (10% of smokers) attended stop smoking clinics and 16 (4%) individuals were recorded as having quit smoking. Discussion: The simple intervention of asking PLWH about tobacco smoking and offering referral to smoking cessation services rapidly identified current smokers, 40% of whom accepted referral to smoking cessation services. This highlights the importance of promoting behaviour and lifestyle changes with every contact with health services. However, a large proportion of those referred were either not seen in local services or the outcome of referral could not be ascertained. If the risk of smoking-related morbidity among PLWH is to be reduced, more sustainable referral pathways and ways of improving uptake of smoking cessation services must be developed.